Rola środowiska przyrodniczego w procesach gospodarowania i rozwoju ekonomicznego w szkole historycznej - Czaja, Stanisław; Cymerman, Anna (Natural Environment in the Economic Processes and Economic Growth in the Historical School, 2005)
The article has presented the ideas of Historical School on the role of natural environment in the economic processes and in the economic growth. There are ideas which were developing in the Old- and New Historical School and were very important for the theory of economics, environmental economics and economic geography.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 60-68